Newborn with a genital cystic lesion - Mafalda Cascais; Diana Coimbra; Patrícia Miranda; Joaquim Tiago; Raquel Henriques; Rosa Ramalho (BMJ Publishing Group, 2019)
Interlabial cysts in the newborn are rare findings and distinct entities are included in the differential diagnosis. Simple hymenal cysts are one of the most commonly reported and spontaneous regression frequently occurs. We report a case of a newborn with an introital cyst arising from the hymen.